Physicochemical properties of Kalahari melon seed oil following extractions using solvent and aqueous enzymatic methods - Nyam, Kar Lin; Tan, Chin Ping; Che Man, Yaakob; Lai, Oi Ming; Long, Kamariah (Institute of Food Science and Technology, 2009)
The physico‐chemical properties of oil from Kalahari melon seed were determined following extraction with petroleum ether and aqueous‐enzymatic methods. Two different enzymes Flavourzyme 1000 L and Neutrase 0.8 L were separately used during aqueous‐enzymatic method. The free fatty acid, peroxide, iodine and the saponification values of the oils extracted using the methods were found to be significantly (P < 0.05) different. The melting point of the oils extracted was in the range of −18.7 °C to −17.5 °C and no significant (P > 0.05) difference between the oil obtained from solvent and aqueous‐enzymatic extractions was observed. Enzyme‐extracted oil tended to be light‐coloured and more yellow in colour compared with solvent‐extracted oil. The predominant fatty acids in the extracted oils were linoleic acid (62.2–63.1%), with some oleic (16.8–17.1%), palmitic (11.4–12.4%), stearic (7.5–8.1%), linolenic (0.7–1.2%) and eicosenoic (0.3%). Phenolic acids in enzyme‐extracted oils were comparable to the solvent‐extracted oil. The oils extracted with these two methods were differed in the composition of their phytosterol and tocopherol contents, but no significant (P > 0.05) difference between the two enzyme‐extracted oils was observed.